Forensic aspects of injuries resulting from cardiopulmonary resuscitation. - Charaschaisri, W. (Chulalongkorn Medical Journal, 2023)
In 1960, Kouwenhoven observed that forceful compressions on the chest could produce an arterial pulse. Over the following years, cardiopulmonary resuscitation (CPR) became continuously advanced. Currently, experts at the conference on International Guidelines 2010 strongly recommend development of in-school CPR programs as a primary educational strategy to ensure wide-spread learning of CPR. During CPR the physician always gives priority to dealing with the life-threatening condition first. While CPR can save lives, it may also expose a high risk of injury to the patient. As a result, forensic pathologists often find CPR-related injuries during autopsies that are unrelated to the patients’ primary cause of death. CPR-related injuries can be classified as bruising and abrasions in the face and neck, fractures of the hyoid bone and thyroid cartilage, airway injuries, vomitus aspiration, positional error of the tube for intra-tracheal intubation, petechiae, retinal hemorrhages, subarachnoid hemorrhages, rib and sternum fractures, bone marrow embolism, cardiac injuries including myocardial hemorrhages and frothy heart blood, and injuries to the abdominal organs such as the liver and spleen. If CPR-related injuries are not widely known to a sufficient degree it may cause various problems for both clinical and postmortem investigations. Therefore, forensic pathologists must be able to distinguish between CPR-related injuries and similar injuries caused by other factors, such as assault or accidental violence. Recently, there is an increasing amount of autopsies to determine whether there is medical malpractice associated with CPR preceding death. A good knowledge of CPR and its related adverse effects are therefore essential for forensic pathologists in order to give an accurate medical expert opinion.